Early treatment interruption and nutritional status as predictors of mortality in Mycobacterium avium complex pulmonary disease - Hye Young Hong; Youngmok Park; Song Yee Kim; A La Woo; Hye-Jeong Lee; Young Ae Kang (PLoS ONE, 2026)
Mycobacterium avium complex pulmonary disease (MAC-PD) requires prolonged multidrug therapy. However, treatment outcomes remain suboptimal due to limited antibiotic efficacy, disease chronicity, and frequent early treatment interruption (ETI). Despite its clinical significance, data on the prevalence, risk factors, and long-term outcomes of ETI remain limited. Therefore, this study aims to identify factors associated with ETI and its impact on mortality. A retrospective cohort study of 420 patients treated with MAC-PD was conducted between 2010 and 2023. Patients were categorized into ETI (treatment duration < 12 months) and standard groups (treatment duration ≥ 12 months). Logistic regression was used to identify risk factors for ETI, whereas multivariate Cox proportional hazards regression was employed to evaluate factors associated with mortality. ETI occurred in 30% of patients. Low prognostic nutritional index (PNI) (adjusted odds ratio [aOR]: 0.92; 95% confidence Interval [CI]: 0.87–0.99) and grade 2 or higher adverse drug reactions (ADRs) (aOR: 5.65; 95% CI: 2.45–15.00) increased the risk of ETI. ETI was associated with higher mortality (adjusted hazard ratio: 2.86; 95% CI: 1.51–5.40). Additionally, low PNI scores indicated increased mortality risk. ETI is prevalent in MAC-PD and is strongly associated with ADRs and poor nutrition, both of which also predict higher long-term mortality. Early ADR monitoring and nutritional support are essential for improving treatment adherence and patient outcomes.